2022
DOI: 10.48048/tis.2022.4949
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the Medicinal Mushroom Ganoderma resinaceum in Iraq, Morphological, Molecular Identification and Production of Basidiocarps on Novel Media

Abstract: Ganoderma was isolated from an apple tree in the Tikrit region (Iraq), according to phenotypic characters and phylogenetic analyses based on internal transcribed spacer ITS 1 - 5.8S - ITS4 rDNA sequences, this isolate identified as G. resinaceum and registered with accession number MN448375 in the NCBI Database. We described a novel media for artificial cultivation of G. resinaceum, composed of wheat straw as basic substrate amended with premix (paper wastes, poplar sawdust and rice hulls at 1:1:1 (W:W:W) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…]10[.cultivated Pleurotus sp. on a mixture of sunflower seed husks with wheat straw at a ratio of 1:1 it was found that the growth of mycelium increased by 13-25% compared to wheat straw only, accordingly, there is a close relationship between the IOP Publishing doi:10.1088/1755-1315/1158/7/072023 11 abundance of fungal growth with the metabolic products, this was also confirmed by previous studies [32,33].…”
Section: Discussionsupporting
confidence: 81%
“…]10[.cultivated Pleurotus sp. on a mixture of sunflower seed husks with wheat straw at a ratio of 1:1 it was found that the growth of mycelium increased by 13-25% compared to wheat straw only, accordingly, there is a close relationship between the IOP Publishing doi:10.1088/1755-1315/1158/7/072023 11 abundance of fungal growth with the metabolic products, this was also confirmed by previous studies [32,33].…”
Section: Discussionsupporting
confidence: 81%
“…After obtaining the pure mycelium of different Ganoderma spp. isolates, spawn was prepared using sterilized wheat grains, according to [9].…”
Section: Preparation Of Ganoderma Spp Spawnmentioning
confidence: 99%
“…Three bags for each treatment were incubated in a mushroom production room at 25 ±2°C. All fruit body production conditions were applied as mentioned by [9]. Table 1.…”
Section: Cultivation Of Ganoderma Spp On Local Organic Waste (Solid M...mentioning
confidence: 99%
See 2 more Smart Citations